ADOLESCÊNCIA PROLONGADA: UM OLHAR SOBRE A NOVA GERAÇÃO - Alessandra Oliveira (Universidade do Oeste Paulista, 2007)
The present article investigates the current modifications happened in the considered people's lifestyle adult. It is known that the human development is not static, because it accompanies the time and culture in that it is inserted, involving the search of the identity, autonomy and the person's ripening. In this context the happened changes reflect a new way of living in the current society. This study looked for to investigate causes and consequences of that phenomenon, once there is little literature regarding the subject.